Medication adherence among chronic kidney disease patients in Hospital Universiti Sains Malaysia - Malek, Nurainni Abdul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Medication adherence is defined as “the extent to which a person’s behaviour corresponds with the agreed recommendations of a healthcare provider in terms of taking medicines, following the recommended diet and/or executing lifestyle changes”. As medication adherence is important to slow the disease progression and prevent complication especially among Chronic Kidney Disease (CKD) patients, a cross-sectional study was carried out to assess the medication adherence among CKD patients in Hospital USM. Data was collected using a self-administered questionnaire. A total of 75 CKD patients from Klinik Pakar Perubatan (KPP) and Chronic Kidney Disease (CKD) Resource Centre in Hospital USM, who fulfilled the inclusion criteria were involved in this study. They were selected through probability simple random sampling method. Data collected were statistically analysed using the Statistical Package Social Science (SPSS) software version of 25. This study shows that 44.0% of the CKD patients in Hospital USM had low medication adherence. Moreover, the results showed that 85.3% of respondents had a good satisfaction level on medication information provided by both medical officer and pharmacists. While 74.7% of the respondents had a good satisfaction level with information from the nurses. Ethnicity was found to be significantly associated to non-adherence to medication (p = 0.032). Forgetfulness, busy and missed appointments were found to be the most common reasons for non-adherence among CKD patients in Hospital USM. In conclusion, suitable management and strategies should be developed and improve to minimise barriers to medication adherence among CKD patients